A review on the Atomic Energy Licensing Act 1984 and the Atomic Energy Licensing (Radioactive Waste Management) Regulation 2011 on the radioactive waste in Malaysia / Muhammad Mustafa Mohd Zin, Arizan Abdul Rahman and Mohamad Haziq A. Rahman - Mohd Zin, Muhammad Mustafa; Abdul Rahman, Arizan; A. Rahman, Mohamad Haziq (2012)
This project paper analyses the Atomic Energy Licensing Act (Act 304) 1984 and the Atomic Energy Licensing (Waste Management) Regulation 2011 for governing radioactive waste management in Malaysia. The analysis covers both strengths and weaknesses of the radioactive waste management as a preparation for Malaysia in the future i.e. should Malaysia choose to venture into nuclear energy and built a nuclear power plant. The aim of this project paper is to review the present laws and highlight the changes that it needed. In doing so, this project paper makes several comparisons with the laws of other countries and also international law. It is to ensure that Malaysia will obtain vast knowledge for the radioactive waste management in the future. The methodology used for this study is qualitative in nature using the library as a main source. Primary and secondary sources was gathered and analysed. A comparative study was carried out with the radioactive waste management laws in the United States of America and Malaysia. The finding of this project is hopeful as an added material for future research in this area. As a conclusion, the research that has been conducted is hoped to be able to help the development of laws and guidelines for an environment friendly and safe nuclear power plant in Malaysia. A comprehensive legal framework is paramount in order to meet local demand for nuclear power plant and radioactive waste management.